A STUDY ON THE IMPACT OF COVID-19 CRISIS ON THREE-FOUR STAR HOTELS IN MYANMAR - Oo, Tin May; Batra, Adarsh (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The study aims to understand how three stars and four stars hotels in Myanmar survive during COVID-19 outbreak and impact of COVID-19 crisis on three stars and four stars hotels in Myanmar. The researcher used qualitative analysis methods, by semi-structured in-depth interviews, collected raw data from sixteen local guests, one long-stay foreigner and five hotel managers in Mandalay and Muse during May to August 2020. To analyses the data, the study used thematic analysis method. The findings of the study are that all three-star and four-star hotels in Myanmar follow safety instruction and internationally-accepted safety standard to ensure the health, safety and well-being of the hotels’ guests and employees. Hotels were using hospital-grade disinfectants and disinfected common area inside the hotel three times a day. Hotel staff are requested to wear a face shield, mask, gloves and PPE suit. From the guest’ perspective, every hotel at least had to implement WHO protocols because they have high expectations of hygiene, cleanliness and safety before and during their stay. Keywords: Covid-19Hospitality and tourism industryHygieneSafety management measures; afety standard